Implications of the serine protease HtrA1 in amyloid precursor protein processing - Grau, Sandra (National Academy of Sciences, 2005)
The defining features of the widely conserved HtrA (high temperature requirement) family of serine proteases are the combination of a catalytic protease domain with one or more C-terminal PDZ domains and reversible zymogen activation. Even though HtrAs have previously been implicated in protein quality control and various diseases, including cancer, arthritis, and neuromuscular disorder, the biology of the human family members is not well understood. Our data suggest that HtrA1 is directly involved in the β-amyloid pathway as it degrades various fragments of amyloid precursor protein while an HtrA1 inhibitor causes accumulation of Aβ in astrocyte cell culture supernatants. Furthermore, HtrA1 colocalizes with β-amyloid deposits in human brain samples. Potential implications in Alzheimer's disease are discussed.